Sains dalam Al-Hadist: Studi Disiplin Islam dan Sains - Dafi Rasyid Arrayan; Arfadillah Hasri; Maftuh Ajmain (PT. Hasba Edukasi Mandiri, 2026)
This study aims to understand the meaning and position of Al-Hadith in Islam, determine the relationship between science and Al-Hadith, and identify and analyze examples of scientific content in Al-Hadith across various fields of science. The method used is library research with a descriptive-analytical approach to literature related to hadith and science. The results show that Al-Hadith occupies the second position after the Qur'an as a source of law and a guide for Muslim life. The relationship between science and Al-Hadith is harmonious and complementary, with modern science increasingly confirming the truth of the statements of the Prophet Muhammad. The scientific content in Al-Hadith is very broad, covering the fields of health (hand washing, quarantine, honey, fasting), environment (planting trees, water cleanliness, animal protection), astronomy and the universe (origin of the universe, eclipses, wind), as well as social and psychology (influence of environment, power of smiling, danger of anger, healthy sleep patterns). This study proves that Islam is a religion that is in harmony with science and encourages its followers to continue thinking, researching, and developing knowledge.